TASAWUF DAN RESOLUSI MORAL: STUDI TERHADAP IMPLIKASI AJARAN TASAWUF DALAM MENGATASI DEGRADASI MORAL - Muhammad Amin (Fakultas Ushuluddin dan Pemikiran Islam Universitas Islam Negeri Raden Fatah Palembang, 2019)
Moral degradation is a complicated problem to solve. This applies to all nations in the world. Because, moral damage to society in a country can result in the destruction of a nation. For this reason, the urgency to study strategies needs to be done in overcoming this. The conclusion of this paper is: that the teachings in Sufism can be one of the resolutions in overcoming moral degradation. The teaching is implemented in several stages, namely takhalli, tahalli, and tajalli.